Ductilisation of tungsten (W): On the increase of strength AND room-temperature tensile ductility through cold-rolling. (April 2017) - Reiser, Jens; Hoffmann, Jan; Jäntsch, Ute; Klimenkov, Michael; Bonk, Simon; Bonnekoh, Carsten; Hoffmann, Andreas; Mrotzek, Tobias; Rieth, Michael
Abstract: Here we show that cold-rolling is a method to achieve room-temperature ductility in commercial purity, monolithic tungsten (W). Furthermore, we show that a decrease in rolling temperature concomitantly increases the strength and ductility of tungsten. So cold-rolling is a way to overcome the strength–ductility trade-off. In this work, we assess three different cold-rolled microstructures obtained from rolling at (i) 1000 °C (1273 K), (ii) 800 °C (1073 K), and (iii) 600 °C (873 K). Benchmark experiments were performed on a sintered ingot as well as on a hot-rolled plate. From these plates tensile test specimens were cut by spark erosion and tested at room temperature. The results show an increase of total uniform elongation, A ut, ranging from 1.38% (cold-rolled at 1000 °C (1273 K), and 800 °C (1073 K)) up to 1.47% (cold-rolled at 600 °C (873 K)) and an increase of the total elongation to fracture, A t, ranging from approximately 3% (cold-rolled at 1000 °C (1273 K), and 800 °C (1073 K)) up to 4.19% (cold-rolled at 600 °C (873 K)) with decreasing rolling temperature. The microstructure of the plates is analysed by means of scanning electron microscopy (SEM) (grain size, subgrains, crystallographic texture) and transmission electron microscopy (TEM) (bright field imaging, scanning TEM). Furthermore, strain-rate jump tests have been performed at 400 °C (673 K) to determine the strain-rate sensitivity, m, (sintered ingot m  = 0.088, cold-rolled at 600 °C (873 K) m  = 0.011) and the activation volume, V, (hot-rolled W plate V  = 191 b 3, cold-rolled at 600 °C (873 K) V  = 111 b 3 ) of the tungsten sheets. The question of why cold-rolling increases both strength and ductility is discussed against the background of cold-rolling-induced lattice defects. We speculate that the increase of ductility is caused by the ordered glide of screw dislocations, that move with low deformation incompatibility along the high-angle grain boundary (HAGB) channels (confined plastic slip). Graphical abstract: Highlights: 3 tungsten sheets have been cold-rolled: at 600 °C, at 800 °C, and at 1000 °C Tensile tests at RT: A ut and A t increase with decreasing rolling temperature Grain size, d : sintered ingot (10.7 μm), cold-rolled at 600 °C (250 nm, S-direction) Hall-Petch: hardness (HV0.1) and yield strength, σ y, are proportional to 1 / d SRS, m, at 400 °C: sintered ingot (0.088), cold-rolled at 600 °C (0.011)